Verdi's Rigoletto - Verdi, Giuseppe, 1813-1901 (Opera Journeys, 2002)
A comprehensive guide to Verdi's RIGOLETTO, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 35 music highlight examples.
Libretto by Francesco Maria Piave based on Le Roi s'amuse by Victor Hugo.
Keywords: Verdi, Giuseppe, -- 1813-1901. -- Rigoletto.; Rigoletto (Verdi, Giuseppe); Operas -- Librettos.; Opéras -- Livrets.; MUSIC -- Genres & Styles -- Opera.; Operas -- Librettos